GE_GERICHTE A/1421/2022 vom 10. August 2018 - GE Cour de justice (2018)
EXCÈS DE VITESSE;FAUTE GRAVE;ÉTAT DE NÉCESSITÉ;NÉCESSITÉ;PROFESSION;PROCÉDURE PÉNALE | LCR.16c.al1.leta; LCR.90.al2; LCR.16c.al2.leta; LCR.16.al3; CP.17